Assessment of knowledge, attitude and practice towards sustainable consumption among university students in Penang, Malaysia - Mokhtar, Nur Ainul Shuhada; Kamarul Zaman, Nur Qamarina Ain; Zawawi, Nurul Amira Shafira; Salehfuddin, Wan Amyzatul Aida; Zakaria, Alia Qistina; Ali, Nurul Syifa Aqila; Mohd Aminuddin, Murni Amirra; Nazli, Siti Nurshahida; Sabri, Nurhidayah; Tengku Ibrahim, Tengku Nilam Baizura (Universiti Teknologi MARA (UiTM), 2025)
The study aimed to assess the knowledge, attitude, and practice of sustainable consumption among university students in Penang, Malaysia. Sustainable consumption is one of the crucial goals in Sustainable Development Goals that foster environmentally friendly behaviour in the Malaysian community. mitigating negative impacts of consumption patterns. A quantitative data collection took place over five days by distribution of online questionnaires to a diverse sample of students, evaluating their knowledge of sustainable consumption principles, attitudes towards sustainable lifestyles, and actual consumption practices. The preliminary findings showed a high level of knowledge among university students regarding sustainable consumption principles. However, there were variations in attitudes towards sustainable lifestyles, with some showing moderate commitment while others exhibited a more indifferent approach. A gap between knowledge and practice was identified, indicating disconnection between students' comprehension regarding sustainable consumption and their implementation of sustainable behaviours. Influential factors, such as personal values, perceived barriers, social norms, and awareness of sustainable alternatives, shaped students' knowledge, attitude, and practice towards sustainable consumption. The role of educational institutions, peers, and media in promoting sustainable consumption was also found to be significant